Macrophage Activation Syndrome as Onset of Systemic Lupus Erythematosus: A Case Report and a Review of the Literature - Granata, Guido (Hindawi Publishing Corporation, 2015)
Macrophage activation syndrome (MAS) is a potentially fatal condition. It belongs to the hemophagocytic lymphohistiocytosis group of diseases. In adults, MAS is rarely associated with systemic lupus erythematosus, but it also arises as complication of several systemic autoimmune disorders, like ankylosing spondylitis, rheumatoid arthritis, and adult-onset Still's disease. Several treatment options for MAS have been reported in the literature, including a therapeutic regimen of etoposide, dexamethasone, and cyclosporine. Here we report a case of 42-year-old woman in whom MAS occurred as onset of systemic lupus erythematosus.